Price Concentration: New Evidence from Greek Industries and the Cournot Model - Apergis, Nicholas; Monastiriotis, Vasilios (Economic Society of Australia, 2013)
This paper investigates the degree of competitive forces across Greek industries over the period 2000–2011 at the three-digit SIC level. Based on the simple Cournot modelling approach, three alternative models are used to investigate the competitive conditions across industries. The empirical results indicate that the majority of Greek industries, with the exception of the Chemicals industry, operate in non-competitive conditions.